Estimating the effect of trade facilitation implementation on trade misinvoicing-based illicit financial flows and tax revenue in Asia and the Pacific - Alexey Kravchenko; Yann Duval (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
Trade misinvoicing occurs when price, quantity or description of internationally traded goods is purposefully misrepresented for pecuniary gain. It is one type of illicit financial flows (IFFs), and combating IFFs has been explicitly included in the Sustainable Development Goals. Most literature on the topic so far focused on understanding and estimating misinvoicing. This study examines whether, as previously hypothesised, digital trade facilitation, in particular cross-border trade data exchange, can help in addressing misinvoicing. The study builds a simple index of misinvoicing at harmonized system (HS) four-digit level using UN Comtrade data for 2015, 2017 and 2019 to match the UN Global Survey on Digital and Sustainable Trade Facilitation data, together with a number of standard control variables commonly included in trade-related regression analyses. The results suggest that there is indeed a statistically significant association between misinvoicing as measured by the index and rates of implementation of various trade facilitation measures. The study proceeds to estimate a range of the impact of full implementation of trade facilitation measures (own and trade partners') on tax revenue, estimated to be at least 119 billion to 183 billion for countries in the Asia-Pacific region, per year. Notably, this is likely to be an underestimate because of the aggregation bias of analysis conducted at HS four-digit level. Nevertheless, these numbers provide a defendable, theoretically and logically consistent estimates supporting the argument that economies stand to gain significantly from exchanging trade data across borders to stem trade misinvoicing. Implementation of cross-border paperless trade measures promise to offer the most impact on tax revenues.
Keywords: F14; H26; 330; Illicit financial flows (IFFs); trade misinvoicing; trade facilitation; Asia-Pacific